Expression of modified rye ribosomal RNA genes in wheat - Gustafson, J. P. (1988)
Several wheats (Triticum aestivum L. em Thell.) containing the short arm of chromosome 1R from rye (Secale cereale L.) translocated to the long arm of wheat chromosome 1B were examined, by in situ hybridization with a biotinylated probe, for the expression of rye rRNA genes located in the nucleolus-organizing region (NOR) present on the short arm of 1R. The wheats analyzed contain a reduced rye NOR band, identified by a C-banding technique, that was assumed to have resulted from a deletion that reduced the number of rRNA genes and spacer units. Genes being actively transcribed could be recognized as dispersed label on DNA within the nucleolus, while those genes that were inactive were seen as condensed label. After in situ hybridization with a biotinylated rye NOR spacer probe, no evidence of rye rRNA gene activity was detected in the plants containing a reduced rye NOR band. Biotin-labeling of chromosomes containing a normal-sized rye NOR locus showed a degree of rye activity consistent with the results of a previous study that used a radioactive probe detected by autoradiography. It was determined previously that rye rRNA genes in a wheat background show significantly less activity than in diploid rye because the spacer units between the rRNA genes of rye are smaller than those of wheat, and in cereals the ribosomal locus with the larger spacer unit is preferentially transcribed. The present results indicate that the number of spacer units is also important in determining which NOR locus (i.e., rye or wheat) will be expressed when several ribosomal loci are present in a wheat background.